Encylopedia of analytical chemistry : supplementary S1-S3: applications, theory and instrumentation - Meyers, Robert A. [ (Robert Allen)] , 1936- (John Wiley & son, 2011)
Summary:"This Work is proposed as three supplementary volumes publishing 10 years after the original publication of the Encyclopedia of Analytical Chemistry (EAC). EAC provides a much-needed professional level reference work and is the most comprehensive analytical chemistry reference available, covering all aspects from theory and instrumentation through to applications and techniques"-Provided by publisher